2021
DOI: 10.3389/fonc.2021.732166
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Novel Non-Lytic Cancer Immunotherapy Using a Recombinant Arenavirus Vector Platform

Abstract: Engineered viral vectors represent a promising strategy to trigger antigen-specific antitumor T cell responses. Arenaviruses have been widely studied because of their ability to elicit potent and protective T cell responses. Here, we provide an overview of a novel intravenously administered, replication-competent, non-lytic arenavirus-based vector technology that delivers tumor antigens to induce antigen-specific anti-cancer T cell responses. Preclinical studies in mice and cell culture experiments with human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Due to their high immunogenicity, LCMV vectors have been explored as vaccine candidates for various diseases ( 810 ). In these prior studies, LCMV vectors have been genetically modified to include a foreign antigen to prime antigen-specific immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their high immunogenicity, LCMV vectors have been explored as vaccine candidates for various diseases ( 810 ). In these prior studies, LCMV vectors have been genetically modified to include a foreign antigen to prime antigen-specific immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…A study evaluated the efficacy of HB-200 arenavirus-based immunotherapy combined with pembrolizumab for first-line treatment of HPV16-positive head and neck cancer patients. HB-200 can express non-oncogenic HPV16 E7-E6 fusion protein, inducing E6- and E7-specific CD8+ T cell responses ( Lauterbach et al, 2021 ). The results showed that the combination therapy exhibited promising clinical activity in the first-line treatment setting, with an overall response rate of 43% ( Nabell et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their high immunogenicity, LCMV vectors have been explored as vaccine candidates for various diseases (8)(9)(10). In these prior studies, LCMV vectors have been genetically modified to include a foreign antigen to prime antigen-specific immune responses.…”
Section: Lcmv Vectorsmentioning
confidence: 99%